2014
DOI: 10.1021/jp411348f
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer from Graphene Quantum Dots to the Copper Complex Enhances Its Nuclease Activity

Abstract: We previously reported that graphene oxide could enhance nuclease activity of copper complex containing aromatic ligands, thus exhibit the potential for applications in anticancer therapy. However, the functional mechanism of graphene oxide is not well understood. In this work, using graphene quantum dots (GQDs), which have smaller lateral size, better biocompatibility, and a conjugate state higher than that of graphene oxide, we investigated systematically the mechanism of GQDs in enhancing nuclease activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 40 publications
(90 reference statements)
2
11
0
Order By: Relevance
“…It's still not clear why some radical scavengers are not effective. These inhibition results suggested that hydroxyl radicals might be involved during the reactions, similar to the observations when using the Cu 2+ cofactor . The result is further supported by the enhancement of the reaction rate constants in the presence of H 2 O 2 and ascorbate (Figures S7 and S8).…”
Section: Resultssupporting
confidence: 80%
“…It's still not clear why some radical scavengers are not effective. These inhibition results suggested that hydroxyl radicals might be involved during the reactions, similar to the observations when using the Cu 2+ cofactor . The result is further supported by the enhancement of the reaction rate constants in the presence of H 2 O 2 and ascorbate (Figures S7 and S8).…”
Section: Resultssupporting
confidence: 80%
“…They attributed the high efficiency to the ability of GQDs to intercalate with DNA. Zheng et al carried out further systematic investigations on this cleavage mechanism . They proposed that electron rich GQDs transfer electrons to the metal complex of Cu 2+ , which in turn produces reactive oxygen species upon reduction.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…Recently, diverse strategies have been developed to obtain Cu II complexes that can induce DNA photocleavage. A series of Cu II polypyridyl compounds have been designed with DNA photocleavage activity,1721 and ternary Cu II complexes with DNA‐binder phenanthroline bases and a photoactive ligand have also been prepared to enhance DNA binding and promote DNA cleavage activity 16,22…”
Section: Introductionmentioning
confidence: 99%